Design and Research of a Harvesting Actuator for Camellia oleifera Flowers during the Budding Period - Zechao Wu; Lijun Li; Qing Zhao; Xin Guo; Jun Li (Agriculture, 2022)
The collection of Camellia oleifera flowers is a key foundation of Camellia oleifera flower pollen extraction. Due to the current problems of low efficiency, high labor intensity and the high cost of manual collection of Camellia oleifera flowers, a harvesting actuator was designed. By analyzing the inherent characteristics of the Camellia oleifera flower and the harvesting method, a harvesting structure using a combination of friction roller twisting harvesting and pipeline pneumatic conveying was designed. The geometric model of the Camellia oleifera flower was established and the motion analysis of the flower was carried out, which indicated that the Camellia oleifera flower would tend to a stable state for easy picking after entering the actuator. Using Automatic Dynamic Analysis of Mechanical Systems 2015 software (ADAMS, MSC. Software Corporation, Santa Ana, CA, USA) to simulate the process of Camellia oleifera flower picking, a mechanical analysis was performed in the contact plane to prove the theoretical feasibility of friction roller picking these flowers, and the main influencing factor was obtained as the speed of the friction roller. The test prototype for Camellia oleifera flower picking was built, and the picking experiment was implemented to study the effect of motor speed on the picking time of single Camellia oleifera flowers and the effect of the success rate of the flower picking. The test results show that when the motor speed is 400 r/min, the picking success rate is 96%, the picking time of a single flower is 1.2 s, and the speed of the machine collection of Camellia oleifera flowers is 2.3 times that of manual collection, which proves the realistic feasibility of this picking actuator. This paper provides an important reference and basis for the research and development of a flower harvesting actuator.